Hepatic radioembolization from transradial access: initial experience and comparison to transfemoral access - Kis, Bela (Diagn Interv Radiol, 2016)
PURPOSE: Despite the growing evidence in the cardiology literature that transradial approach has substantial benefits over transfemoral access, this technique is rarely used during interventions in the systemic circulation. The aim of this study was to evaluate the feasibility of transradial approach for hepatic radioembolization and to compare it with transfemoral approach. METHODS: Sixty-four hepatic radioembolizations performed in 50 patients were included in the study. Thirty-three procedures were performed via radial access in 27 patients, and 31 procedures were performed via femoral access in 23 patients. RESULTS: There was 100% technical success in performing hepatic radioembolization in both groups. The majority (97%) of the patients who underwent transradial radioembolization reported preference for radial artery access. The fluoroscopy time was significantly longer (9.45±5.09 min vs. 5.72±3.67 min, P < 0.01) and the radiation dose was significantly higher (597.8±585.2 mGy vs. 302.8±208.3 mGy, P < 0.01) in the radial group compared with the femoral group. The direct cost savings using radial access versus femoral access is approximately $100/procedure. In addition, there was a one hour (50%) shorter postprocedural stay for patients who underwent the transradial procedure. CONCLUSION: Transradial access is feasible for hepatic radioembolization. The transradial approach is cheaper and offers improved patient comfort. However, it is technically challenging, with longer fluoroscopy times and higher radiation doses. Transradial approach should be considered as a primary choice in patients with low platelet count and/or morbid obesity. Transradial access should be in the procedural repertoire of every interventional radiologist.